Tailored exercise and manual therapy versus standardised exercise for patients with shoulder subacromial pain: a feasibility randomised controlled trial (the Otago MASTER trial) - J Haxby Abbott; Daniel C Ribeiro; Zohreh Jafarian Tangrood; Gisela Sole; Ross Wilson (BMJ Open)
Objectives The aim of this study was to assess whether it was feasible to conduct a full trial comparing a tailored versus a standardised exercise programme for patients with shoulder subacromial pain.Design Two-arm, patient-blinded and assessor-blinded, randomised controlled feasibility trial.Methods Twenty-eight participants with shoulder subacromial pain were randomly allocated into one of two intervention groups—tailored or standardised exercise. Participants in the tailored exercise programme received exercises and manual therapy tailored to their scapular and shoulder movement impairments. Participants in the standardised exercise programme received progressive strengthening exercise. The primary outcome measures were (1) the participant recruitment rate; (2) the proportion of participants enrolled from the total number screened; (3) drop-out rates; and (4) adherence to the rehabilitation programme. Other outcome measures were: (5) pain levels; (6) Patient-Specific Functional Scale; (7) the Shoulder Pain and Disability Index; and (8) pain self-efficacy. We compared changes in pain and disability scores between groups using a repeated mixed-model analysis of variance. Since this is a feasibility study, we did not adjust alpha for multiple comparisons, and considered 75% CI as the probability threshold at 3-month follow-up. Health-related quality of life was assessed using the Short-Form 12 and quality-adjusted life years (QALYs) were estimated.Results The recruitment rate was 3 participants per month, the proportion of participants enrolled was 23%, the drop-out rate was 14% and the overall adherence to the rehabilitation programme was 85%. No between-group differences were found for most outcome measures. Adverse events (n=2, only in the tailored group) were minor in nature and included skin injury or pain following taping.Conclusions Our feasibility trial showed that additional strategies are required for improving recruitment, enrolment and minimising drop-out of participants into the trial and making it feasible to conduct a full trial.Trial registration number ANZCTR: 12617001405303.